Gut dysbiosis in cancer immunotherapy: microbiota-mediated resistance and emerging treatments - Eiman, Liza; Moazzam, Khadija; Anjum, Sumaira; Kausar, Humera; Sharif, Elham Abdullatif M.; Ibrahim, Wisam Nabeel (Frontiers in Immunology, 2025)
Cancer is a multifaceted disease driven by a complex interplay of genetic predisposition, environmental factors and lifestyle habits. With the accelerating pace of cancer research, the gut microbiome has emerged as a critical modulator of human health and immunity. Disruption in the gut microbial populations and diversity, known as dysbiosis, has been linked with the development of chronic inflammation, oncogenesis, angiogenesis and metastasis. This review discusses the microbial species associated with various types of cancer and the pathways involved in their tumorigenic effect including mechanisms like inflammatory cytokine response, immune modulation, genotoxicity and modification of the tumor microenvironment. Diagnostic tools such as metagenomics, metabolomics, and the use of dysbiosis indexes help in the detection of gut bacterial imbalances, enabling early detection of cancer and potential intervention. Gut dysbiosis diminishes the efficacy of cancer treatments including immunotherapies, and creates immunotherapy resistance by altering drug metabolism and driving immunometabolic reprogramming, allowing tumor cells to evade immune attack. Immunometabolic reprogramming through gut microbiota modulation provides a new avenue to be explored that can restore anti-tumor immunity and reverse resistance to cancer treatments. This review also highlights the use of fecal microbiota transplantation and probiotics to mitigate chances of dysbiosis-related cancer progression. Through a comprehensive assessment of the role of gut microbiota in cancer, this review underscores the need for the use of gut microbial biomarkers for cancer detection and microbiome-targeting strategies to individualize cancer treatment.